Risk and Return Analysis on Cryptocurrency Investment - Hardiyanti, Siti Epa (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
The global crypto market has garnered attention from investors due to its high return potential, yet the extreme volatility and associated risks pose significant concerns. This study aims to analyze the risks and returns of cryptocurrency investments using a quantitative approach on global crypto market data. The methods employed include volatility analysis using the GARCH model, as well as risk and return evaluation through CAPM. The results indicate that cryptocurrencies exhibit significantly higher volatility compared to traditional assets, with substantial return potential but accompanied by high risk. These findings imply the need for stricter diversification strategies and risk management for crypto investors to optimize returns and minimize losses.